Economic Reforms; Indian Experience - "Saksena, K D" (Delhi, 2006)
It analyses the performance of the Indian economy during a decade of wide ranging economic reforms, which commenced in mid-1991, as compared to its behaviour in the eighties when some piecemeal measures of liberalization had been taken.
Keywords: Economic Reforms-India